Analisis Sistem Pengereman Mobil Truk Mitsubishi Fuso Type 125Ps Menggunakan Alat Axle Load Breaker Tester di Dinas Perhubungan Kota Cilegon - Aditya Rahman; Irwanto, Irwanto (Fakultas Teknik UMRI, 2024)
This study aims to determine the working system of the Mitsubishi Fuso type 125Ps truck brakes using a brake test tool, namely the Axle Load Breaker Tester at the Cilegon City Transportation Agency. This study uses a direct experimental method using motor vehicle subjects, namely the Mitsubishi Fuso type 125Ps truck. There are 3 data taken, namely the foot brake on axle 1, the foot brake on axle 2 and the hand brake on axle 2. There is also total data on the overall test results which are used to decide whether the final result of the vehicle passes or fails the test and there is also data on the imbalance or deviation between the right and left wheels. There are 2 displays produced from this test, namely by using the existing formula and seeing the results directly on the monitor screen. The results of these two displays are slightly different, perhaps due to several factors including tolerance on the tool, lack of calibration on the tool and age factors on the tool. However, from the differences in these results, the data obtained shows that this vehicle has met the roadworthiness requirements in accordance with existing regulations. This periodic testing is carried out at least once every 6 months so that the braking system works optimally and does not cause accidents for the driver or others.